Computed Tomography–based Measurement of Herniated Orbital Volume Following Acute Orbital Fractures - Erina Kawabata, MD; Takashi Nuri, MD, PhD; Tatsuya Ichida, MD; Koichi Ueda, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. To predict which patients will develop more than 2 mm of enophthalmos and require surgery after orbital fracture is challenging. Although high herniated orbital volume (HV) might be a predictor, its measurement can be complex and time-consuming. This study aimed to identify a simple, reliable, and clinically applicable method for measuring herniated orbital volume. Methods:. This single-center retrospective study examined HV and approximate volume in 42 patients with an orbital floor fracture (OF group) and 56 patients with a medial wall fracture (MW group). Approximate herniated volume (AV) was calculated as a rectangular parallelepiped, quadrangular pyramid, or hemiellipsoid. The correlation between HV and AV was analyzed quantitatively. Receiver operating characteristic curve analysis was performed to compare AV and HV cutoff values. Results:. AV calculated as a hemiellipsoid (AVhe) provided the closest approximation to HV. Correlation analysis showed a positive linear relationship between HV and AVhe in both the OF group (r = 0.818) and the MW group (r = 0.84). The optimal AVhe cutoff value was 1.013 mL in the OF group (positive and negative predictive values, 96.3% and 66.7%, respectively; area under the curve, 0.925) and 1.13 mL in the MW group (positive and negative predictive values, 90.0% and 69.2%, respectively; area under the curve, 0.956). High HV was defined as greater than 1.0 mL in the OF group and greater than 0.9 mL in the MW group. Conclusions:. A simplified method that approximately calculates the volume of herniated orbital contents in a hemiellipsoid pattern model proved to be practical, easy, and reliable.